Dual Transcriptomic Analyses Unveil Host–Pathogen Interactions Between Salmonella enterica Serovar Enteritidis and Laying Ducks (Anas platyrhynchos) - Zhang, Yu; Song, Lina; Hou, Lie; Cao, Zhengfeng; Vongsangnak, Wanwipa; Zhu, Guoqiang; Xu, Qi; Chen, Guohong (Frontiers in Microbiology, 2021)
Salmonella enteritidis (SE) is a pathogen that can readily infect ovarian tissues and colonize the granulosa cell layer such that it can be transmitted via eggs from infected poultry to humans in whom it can cause food poisoning. Ducks are an important egg-laying species that are susceptible to SE infection, yet the host-pathogen interactions between SE and ducks have not been thoroughly studied to date. Herein, we performed dual RNA-sequencing analyses of these two organisms in a time-resolved infection model of duck granulosa cells (dGCs) by SE. In total, 10,510 genes were significantly differentially expressed in host dGCs and 265 genes were differentially expressed in SE over the course of infection. These differentially expressed genes (DEGs) of dGCs were enriched in the cytokine-cytokine receptor interaction pathway via KEGG analyses, while the DEGs in SE were enriched in the two-component system, bacterial secretion system, and metabolism of pathogen factors pathways as determined. A subsequent weighted gene co-expression network analysis revealed that the cytokine-cytokine receptor interaction pathway is mostly enriched at 6 hours post-infection (hpi). Moreover, a number of pathogenic factors identified in the pathogen-host interaction database (PHI-base) were upregulated in SE, including genes encoding the pathogenicity island/component, type III secretion, and regulators of systemic infection. Furthermore, an intracellular network associated with the regulation of SE infection in ducks was constructed and 16 cytokine response-related dGCs DEGs (including IL15, CD40, and CCR7) and 17 pathogenesis-related factors (including sseL, ompR, and fliC) were identified, respectively. Overall, these results not only offer new insights into the mechanisms underlying host-pathogen interactions between SE and ducks, but may also aid in the selection of potential targets for antimicrobial drug development.